Intranasally inoculated bacterium-like particles displaying porcine epidemic diarrhea virus S1 protein induced intestinal mucosal immune response in mice - Su, Kai; Wang, Yawen; Yuan, Chen; Zhang, Yanan; Li, Yanrui; Li, Tanqing; Song, Qinye (Frontiers in Immunology, 2023)
Porcine epidemic diarrhea virus (PEDV) causes acute watery diarrhea and high mortality in newborn piglets. Activation of intestinal mucosal immunity is crucial to anti-PEDV infection. To develop a vaccine capable of stimulating intestinal mucosal immunity, we prepared a bacterium (Lactococcus lactis)-like particle (BLP) vaccine (S1-BLPs) displaying the S1 protein, a domain of PEDV spike protein (S), based on gram-positive enhancer matrix (GEM) particle display technology. We further compared the effects of different vaccination routes on mucosal immune responses in mice induced by S1-BLPs. The specific IgG titer in serum of intramuscularly immunized mice with S1-BLPs was significantly higher than that of the intranasally administered. The specific IgA antibody was found in the serum and intestinal lavage fluid of mice vaccinated intranasally, but not intramuscularly. Moreover, the intranasally inoculated S1-BLPs induced higher levels of IFN-γ and IL-4 in serum than the intramuscularly inoculated. In addition, the ratio of serum IgG2a/IgG1 of mice inoculated intramuscularly was significantly higher with S1-BLPs compared to that of with S1 protein, suggesting that the immune responses induced by S1-BLPs was characterized by helper T (Th) cell type 1 immunity. The results indicated that S1-BLPs induced systemic and local immunity, and the immunization routes significantly affected the specific antibody classes and Th immune response types. The intranasally administered S1-BLPs could effectively stimulate intestinal mucosal specific secretory IgA response. S1-BLPs have the potential to be developed as PEDV mucosal vaccine.